MANAJEMEN BUDIDAYA UDANG VANAME MELALUI PENERAPAN METODE SFA (Stochatisc Frontier Analysis) MELALUI PELATIHAN DI DESA MOOTINELO KWANDANG GORONTALO UTARA - Nento, Wila Rumina; Lamadi, Arafik; Djibran, Moh. Muchlis (Universitas Mataram, 2024)
Shrimp ponds in Mootinelo Village are still classified as conventional with traditional management methods. In addition to the inadequate level of knowledge of the farmers, the quality of the environment is less supportive, disease attacks, and non-standard feeding are also factors that cause vaname shrimp production in Mootinelo Village is not optimal, which of course affects the income of the farmers who are still classified as moderate and even low. In accordance with the objectives of this PMM, namely increasing community productivity with a technical efficiency approach, namely SFA (Stochastic Frontier Analysis), so that the main problems faced by partners, namely aspects of basic knowledge about the technical cultivation of vaname shrimp and aspects of product processing can be overcome. The method used in this training consists of several stages, namely the preparation stage which begins with site observation. Next, the training and counseling stage for participants by delivering material to providing training related to business products. The last stage is the assistance of 10 participants who are vanaem shrimp farmers in the use of DO meters to measure water quality parameters. With an effort to approach technical efficiency, namely SFA (Stochastic Frontier Analysis), the main problems faced by partners, namely aspects of basic knowledge about the technical cultivation of vaname shrimp and aspects of product processing can be resolved. In this case, increasing the knowledge of the 'Vaname Jaya' group of farmers regarding the characteristics and technical efficiency of cultivation through the SFA method, as well as increasing skills in making processed shrimp products, namely eby furrai. In addition, the community was trained in the use of DO meters in measuring pond water quality and making fish feed according to the needs of vanname shrimp whose ingredients consist of fine bran and cornstarch. The conclusion of the results of community service in the form of PMM is that vaname shrimp farming partners have known the factors that affect the technical efficiency and characteristics of aquaculture businesses through the SFA method, and partners can increase the selling value of vaname shrimp through diversification of processed vaname shrimp into eby furai products.